ANALISIS ESTIMASI VOLUME COMBINED CRUDE OIL DALAM PROSES TRANSFER FEED DENGAN METODE QUANTITY ACCOUNTING SYSTEM - Dian Pertiwi, Permata (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2024)
The QAS method combines tank level measurements, oil density, temperature, BS&W content to provide accurate volume estimates. The QAS method ensures that the calculation of the volume of crude oil to be transferred is in accordance with the required standards, thus supporting efficient operations and quality control of the final product. The calculation results of the QAS method are then compared with the results of flowmeter measurements to identify the suitability and potential differences in volume estimates. This study aims to assess the reliability of the QAS method in calculating the volume of crude oil and comparing it with data obtained from the flowmeter during the transfer process. From the analysis results, it was found that the difference in the results between the combined crude oil estimates obtained from the QAS method and the results of direct measurements in the field of PT. KPI RU IV OM 70 Cilacap showed discrepancies of 1.36% for the QAS calculation and 1.38% for the actual measurement in barrels. This shows that the calculation method used in the QAS is able to calculate correction factors accurately, such as temperature and density, so that it approaches the actual volume measured in the field. This study shows that the QAS method is able to provide more comprehensive and reliable volume estimates, especially in the context of density variations and environmental conditions that affect oil volume.